2020
DOI: 10.1101/2020.03.10.985945
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Moderate early-life stress improves adult zebrafish (Danio rerio) spatial short-term memory but does not affect social and anxiety-like responses

Abstract: 5Early-life stress (ELS) is defined as a short or chronic period of trauma, environmental or 3 6 social deprivation, which can affect different neurochemical and behavioral patterns during 3 7 adulthood. Zebrafish (Danio rerio) have been widely used as a model system to understand human 3 8 neurodevelopmental disorders and display translationally relevant behavioral and stress-regulating 3 9systems. In this study, we aimed to investigate the effects of moderate ELS by exposing young 4 0 animals (six weeks post… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 105 publications
(112 reference statements)
1
4
0
Order By: Relevance
“…Thus, we showed that stress caused in the development interval between 20 and 30 dpf did not cause changes in motor patterns. Our results agree with those by Fontana et al ( 2020 ) that used other stressors (water change, shallow water, and overcrowding) applied over 3 days at ~40 dpf. These authors found no effects of stress on locomotor and anxiety-related responses.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, we showed that stress caused in the development interval between 20 and 30 dpf did not cause changes in motor patterns. Our results agree with those by Fontana et al ( 2020 ) that used other stressors (water change, shallow water, and overcrowding) applied over 3 days at ~40 dpf. These authors found no effects of stress on locomotor and anxiety-related responses.…”
Section: Discussionsupporting
confidence: 92%
“…Early-life stress is known to affect neurochemical and behavioral patterns that lead to behavioral issues during adulthood. Some stressors imposed in moderate amounts contribute to increased behavioral flexibility and even improve cognitive performance (Fontana et al, 2020 ). However, some social stressors, such as the one imposed in this study, may trigger brain alterations that affect the proper behavioral repertoire and lead to psychological deficits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In zebrafish, fear-conditioned avoidance learning is a robust phenotype whereby fish exhibit freezing and erratic behavior upon re-exposure to the conditioned stimulus (CS) 73,74 . Although one study found that chronic unpredictable stress did not have any effect on fear conditioning in adult zebrafish 75 , a different ELS protocol found improvement of short-term memory by early life stress when testing in the unconditioned y-maze 76 . Differences in how zebrafish learn fear association are dependent on whether they are reactive or proactive responders to stress, raising the question of how bPAC+ fish's response fits into that spectrum 77 .…”
Section: Discussionmentioning
confidence: 95%
“…For example, intermittent crowding of adult zebrafish has been shown to increase cortisol secretion and reduce their capacity to renew heart tissue after injury (Sallin & Ja zwi nska, 2016), with ramifications for studies of stress responses and tissue regeneration. Temporary crowding has been reported to improve zebrafish working memory (Fontana et al, 2021) with implications for neurobiology, spatial learning and memory research. Further, crowding embryos may lead to hypoxia, which has been shown to result in a higher percentage of malformations and a male-biased F1 generation (Wu, 2009).…”
Section: Social Environmentmentioning
confidence: 99%